The effectiveness of preoperative educational videos on self efficacy and early mobilization implementation in post sectio caesarea mothers - Juliani, Ni Putu; Hartati, Dwi; Anam, Khoirul; Meihartati, Tuti (Institute of Computer Science (IOCS), 2024)
Hospital efforts to increase early mobilization have so far only been through verbal education, but patients still need better Self-Efficacy and elements in carrying out early mobilization. However, early mobilization is very important to speed up post-operative recovery. Early mobilization requires maternal self-efficacy to carry out early mobilization. For this reason, it is necessary to increase self-efficacy by providing pre-operative education using video media so that post-operative patients can immediately mobilize early. This study aims to determine the effectiveness of preoperative educational videos on Self Efficacy and the implementation of early mobilization in mothers after caesarean section. This type of research is quasi-experimental research, and a pre-post-test control group design is used for Self Efficacy, followed by a post-test with a control group for early mobilization. The population is post-cesarean section mothers with an average number of 78 people per month. According to the Roscoe formula, the sample was 34 people, including the intervention and control groups, 17 people each. Data analysis used paired samples t test, independent t test, and Mann-Whitney test. This research shows that preoperative educational videos are effective in increasing Self Efficacy (p-value = 0.008 and average difference = 20.36). Preoperative educational videos are effective in implementing early mobilization in mothers after cesarean section (p-value = 0.008). Conclusion: Preoperative educational videos can increase Self Efficacy and implement early mobilization.